The effect of giving soursop leaves extract (Annona muri cata L.) on Aedes aegypti instar iii larvae - Audina, Miea; Lukiyono, Yauwan Tobing; Wulandari, Devyana Dyah; Romdloni, Muhammad Afwan (Universitas Nahdlatul Ulama Surabaya, 2023)
Aedes aegypti is a mosquito that is a vector for various diseases, including Dengue Hemorrhagic Fever (DHF). Mosquito control can be done in various ways, one of which is using synthetic insecticides, using natural ingredients derived from plants. Soursop leaves are a plant that grows widely in Indonesia and can be used as a natural larvicide. This study aims to determine the effect of giving soursop leaf extract on the death of third instar Aedes aegypti mosquito larvae. The type of research used in this research is experimental with design in this research using the post-test only control design method. The samples used were 25 third instar Aedes aegypti larvae in each of 5 treatments using; negative control (aquadest), positive control (1% abate), soursop leaf extract concentration 25%, concentration 50%, and concentration 75%. With observation times of 3 hours, 6 hours and 24 hours. The data obtained was analyzed using SPSS, a probit test obtained a 3 hours LC50 was 97.653, a 6 hours LC¬50 was 87.697, and a 24 hours LC50 was 53.727. The value of LT50 25% concentration is 42.357, LT50 50% concentration is 24.783, and LT50 75% concentration is 12.996, from the parametric test carried out the results were normal and homogeneous, then the ANOVA test was continued and showed a p-value of 0.02 < 0.05 (significant), then H0 is rejected and H1 is accepted. So it can be said that there is an effect of giving soursop leaf extract on the death of third instar Aedes aegypti mosquito larvae. Researchers are expected to be able to utilize soursop leaves as a natural larvicide that can kill Aedes aegypti larvae.